The Relationship of Inflammatory Indicators and Metabolic Syndrome with Gonarthrotic Cartilage Degeneration: A Novel Glance - Eren Altun; Aziz Atik (Acta Medica Alanya)
Aim: The combination of a number of metabolic abnormalities such as high body mass index (BMI), central obesity, low high-density lipoprotein (HDL), high triglycerides, high blood pressure, and hyperglycemia is defined as metabolic syndrome (MetS). This study aimed to clarify the effect of metabolic syndrome components on joint degeneration and investigate the relationship between systemic inflammatory response and end-stage osteoarthritis clinical course.Material and Methods: Fifty-seven patients, who underwent total knee arthroplasty due to primary knee osteoarthritis, were classified according to metabolic syndrome diagnosis criteria. Their medial and lateral tibial plateau specimens were graded histopathologically according to Osteoarthritis Research Society International scoring system (OARSI).Results: 33 patients were performed right total arthroplasty (57.9%), 24 were performed left (42.1%). The mean age was 68.46 ± 6.88 (range 57 to 85). The mean BMI value was 30.31 ± 5.26 (range 20.2 to 48). According to the International Diabetes Foundation (IDF) 2005 metabolic syndrome (MetS) diagnostic criteria; 31.5% (n = 18) of the patients did not have MetS, while 68.4% (n = 39) had. There was no statistically significant relationship between tibial plateau OARSI scores and metabolic syndrome (p> 0.05). Besides, these OARSI scores and the operation side, hypertension, and BMI had no statistically significant relationship (p> 0.05).Conclusions: Metabolic syndrome components may play a role in initiating the osteoarthritic process via adipokines, but we could not identify certain effects of pro-inflammatory mediator components on tibial plateau cartilage degeneration with histopathological scores till end-stage arthritic progress.